Drama, Performance Ethnography, and Self-Esteem: Listening to Youngsters With Dyslexia and Their Parents. (12th May 2014) - Antonelli, Liam; Bilocca, Sasha; Borg, Dario; Borg, Shane; Boxall, Mark; Briffa, Luke; Debono, Charlene; Falzon, Ruth; Farrugia, Valentina; Gatt, Leah; Formosa, Mike; Mifsud, Dione; et al.
Self-esteem affects learning, performance, self-worth, and quality of life, particularly in persons with dyslexia, or rather how students with dyslexia are mis/understood and supported. Dyslexia does not only affect literacy but also affects emotional well-being. Webb concludes that for children to feel successful, they need to become aware of their unique learning strengths to apply them effectively to strengthen weaknesses. Drama and Performance Ethnography (PE) can be support strategies. Workshops were carried out with a group of adolescent youngsters with dyslexia. The aim was to provide a safe environment where they could find their voice and gain self-confidence through drama and PE to provide opportunities to address self-esteem and to provide insights for policies and practice. This article intends to listen to these youngsters', also co-authors, and their parents' narratives of this experience.